2010
DOI: 10.1007/s10551-010-0554-6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Ethical Values, Group Creativity, Job Satisfaction and Turnover Intention: The Impact of Work Context on Work Response

Abstract: A corporate culture strengthened by ethical values and other positive business practices likely yields more favorable employee work responses. Thus, the purpose of this study was to assess the degree to which perceived corporate ethical values work in concert with group creativity to influence both job satisfaction and turnover intention. Using a self-report questionnaire, information was collected from 781 healthcare and administrative employees working at a multi-campus education-based healthcare organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
126
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(161 citation statements)
references
References 111 publications
(122 reference statements)
14
126
1
9
Order By: Relevance
“…Several studies have also provided empirical support for the notion that a higher level of organizational ethics is associated positively with different individual outcomes, such as better job satisfaction (Jaramillo, Mulki, & Solomon, 2006;Pettijohn, Pettijohn, & Taylor, 2008;Valentine et al, 2011) and higher organizational commitment (e.g., Huhtala, Feldt, Hyvönen, & Mauno, 2013;Sharma, Borna, & Stearns, 2009;Treviño et al, 1998;Valentine, Godkin, & Lucero, 2002), which can reduce employees' turnover intentions (e.g., Jaramillo et al, 2006;Pettijohn et al, 2008;Valentine et al, 2011). Huhtala et al (2011) showed that ethical culture was associated with less ethical strain, less emotional exhaustion (the core dimension of burnout), and higher work engagement at the individual level.…”
Section: Ethical Culture As a Context For Well-beingmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have also provided empirical support for the notion that a higher level of organizational ethics is associated positively with different individual outcomes, such as better job satisfaction (Jaramillo, Mulki, & Solomon, 2006;Pettijohn, Pettijohn, & Taylor, 2008;Valentine et al, 2011) and higher organizational commitment (e.g., Huhtala, Feldt, Hyvönen, & Mauno, 2013;Sharma, Borna, & Stearns, 2009;Treviño et al, 1998;Valentine, Godkin, & Lucero, 2002), which can reduce employees' turnover intentions (e.g., Jaramillo et al, 2006;Pettijohn et al, 2008;Valentine et al, 2011). Huhtala et al (2011) showed that ethical culture was associated with less ethical strain, less emotional exhaustion (the core dimension of burnout), and higher work engagement at the individual level.…”
Section: Ethical Culture As a Context For Well-beingmentioning
confidence: 98%
“…In the present study we focus on ethical culture because it is an example of a virtuous environment, an environment characterised by moral values, assumptions and beliefs. This is also significant in supporting well-being, as the cultural context can have a profound effect on levels of stress and attitudes toward work (Peterson & Wilson, 2002), and ethical values can promote positive interactions among employees (Valentine, Godkin, Fleischman, & Kidwell, 2011). Ethical culture has been shown to relate to better well-being among managers (Huhtala, Feldt, Lämsä, Mauno, & Kinnunen, 2011), but evidence on the level of the organization, based on shared experiences, is lacking.…”
Section: Ethical Culture and The Corporate Ethical Virtues Modelmentioning
confidence: 99%
“…Also, the finding that intention to stay does not significantly influence the relationship between ethical culture and employee productivity is in consonance with the findings of Pettijohn, Pettijohn and Taylor (2008) who in their study on "ethical behaviours: Their influence on job satisfaction and turnover intentions", submit that employee intentions relatively influence their ethical behaviour which in turn influence their outcomes such as satisfaction, and productivity. In a more recent study, Valentine, et al (2011) investigated the relationship between "corporate ethical values, group creativity, job satisfaction and turnover intention" and came up with a similar result.…”
Section: Discussionmentioning
confidence: 77%
“…They concluded that employee turnover intentions could negatively affect their perception of ethical culture. Similarly, Valentine, et al (2011) died "Corporate ethical values, group creativity, job satisfaction and turnover intention", and submit that turnover intention slightly moderate the relationship between corporate ethical culture and the other variables.…”
Section: Ethical Culture Employee Productivity and Intention To Staymentioning
confidence: 99%
“…For this reason, when the factors in job satisfaction of organizational members are properly controlled, remedial measures could be adopted to enhance employees' job satisfaction and effectively promote the morale and reduce the turnover rate. It shows positive effects on an organization [4] [5].…”
Section: Introductionmentioning
confidence: 97%